THE PROTEST POTENTIAL OF ENVIRONMENTAL ISSUES: NETWORK DETERMINANTS OF THE POLITICIZATION OF ECOLOGY - G. V. Kosov; A. E. Gapich; O. V. Minkina; S. V. Rezhep; S. T. Baranov (Современная наука и инновации, 2022)
The article, based on the results of the author's sociological study, examines the problem of protest moods in several regions of the Russian Federation. The idea is substantiated that environmental problems are triggers of social discontent, the growth of protest moods and, as a result, protests. The idea of the reasons for the politicization of ecologists and the politicization of ecology is grounded. environmental issues, as the fundamental problem of the survival of mankind as a species, as a factor influencing the quality of life of an individual, begins to wilt in the Russian political space, starting from the end of the twentieth century. At the same time, it does not have a serious impact on party doctrines, nor on electoral preferences, nor on the political course of the country as a result. Currently, environmental issues are being updated, its transition to a new quality. It is proved that environmental renewals are a factor, a catalyst, a cause, a condition for the growth of protest moods in the regional community. The idea is substantiated that certain political forces use the environmental agenda in order to consolidate a protest-minded electorate around themselves.